Pigmented Viral-Associated Conjunctival Carcinoma - Norman C. Charles; Brian P. Marr; Susan M. Stenson; Khushbakhat R. Mittal (Case Reports in Ophthalmological Medicine)
A 54-year-old African-American woman developed a pigmented papillary squamous cell carcinoma in the palpebral and bulbar conjunctiva of the right eye in areas that received no sun exposure. In situ hybridization performed on the tumor showed human papilloma virus 16. The left eye showed a pedunculated nonpigmented conjunctival dysplasia. The tumors were extirpated by cryosurgery and topical interferon alfa 2b in the right eye and simple surgical excision in the left eye.